Analysis of Dynamic Fluid Problem-Solving Ability in Prospective Physics Teacher - Adam, Mukhammad Ibnu; Adha, Ahmad Ridlotul; Alfina, Nur Layly; Taqwa, Muhammad Reyza Arief (Proceeding International Conference on Religion, Science and Education, 2025)
This research is focused on analyzing the problem-solving ability of Malang State University students who have taken the basic Fundamental of Physics I course, especially fluid dynamics. The research method used is mix methods model explanatory sequential the method and design used mixed qualitative methods to support quantitative data. Identification uses an instrument in the form of 7-item questions with rubrics or stages of Doctor-Heller problem-solving. The results showed the Usefull Descripion was 76.10%, Physics Approach was 52%, Specific Application of Physics was 49.09%, Mathematical Procedure was 40.00%, and Logical Progression was 24.94%. In the grouping of problem-solving abilities, 9.09% or one student is in the expert problem-solving ability category, 18.18% or two students are in the proficient category, 27.27% or three others are competent, and 18.18% or two students are in the Advance beginner. Some students are still classified as a novice by 27.27% of the remaining respondents. The student’s ability to work on sub-topic items showed that the percentage on the principle of continuity of the relationship between flow velocity and cross-sectional area was 61.81%, the application of the principle of continuity was 58.18%, Bernoulli’s equation on the relationship between flow velocity and fluid pressure was 39, 64%, the relationship of flow velocity, cross-sectional area, and height of 45.82%, application of Bernoulli’s principle to leaky tanks or Toricelli’s theorem of 56.73%, application of Bernoulli’s principle to venturi meter tubes of 38.91% and application of Bernoulli’s principle to pitot tubes by 37.82%. Although this study only focuses on case studies of students’ ability to solve problems according to the Doctor-Heller indicator with interviewees who have difficulty solving problems with novice abilities, suggestions for future research researchers can interview all subjects related to obstacles that occur when doing or conducting research classroom actions.